Regulation of β-adrenergic control of heart rate by GTP-cyclohydrolase 1 (GCH1) and tetrahydrobiopterin - Adlam, D; Herring, N; Douglas, G; De Bono, J; Li, D; Danson, E; Tatham, A; Lu, C-J; Jennings, KA; Cragg, SJ; Casadei, B; Paterson, D; et al. (Oxford University Press, 2012)
Aims Clinical markers of cardiac autonomic function, such as heart rate and response to exercise, are important predictors of cardiovascular risk. Tetrahydrobiopterin (BH4) is a required cofactor for enzymes with roles in cardiac autonomic function, including tyrosine hydroxylase and nitric oxide synthase. Synthesis of BH4 is regulated by GTP cyclohydrolase I (GTPCH), encoded by GCH1. Recent clinical studies report associations between GCH1 variants and increased heart rate, but the mechanistic importance of GCH1 and BH4 in autonomic function remains unclear. We investigate the effect of BH4 deficiency on the autonomic regulation of heart rate in the hph-1 mouse model of BH4 deficiency.